Calculation of proton conductivity at the Sigma 3(111)/[1(1)over-bar0] tilt grain boundary of barium zirconate using density functional theory - Yang, Jin-Hoon; Kim, Byung-Kook; Kim, Yeong-Cheol (ELSEVIER SCIENCE BV, 2015)
We theoretically investigate proton conductivity at the Sigma 3 (111)/[1 (1) over bar0] tilt grain boundary of barium zirconate using density functional theory. In order to evaluate the space charge layer model and the structural disorder model, segregation energies of a +1-charged proton and a +2-charged oxygen vacancy, as well as energy barriers for proton migration, are calculated. The effect of the proton concentration on its segregation is verified and it is found that the segregation energy decreases with increases in the concentration. With consideration of this effect, the segregation energies of the proton and oxygen vacancy are in the range of -0.35 to -0.60 and -0.57 to -0.65 eV, respectively. Based on the segregation energies, an electrostatic potential of 0.51 Vat 600 K is obtained through numerically solving Poisson's equation. An energy barrier range of 0.71-0.95 eV is required for the proton to migrate across the grain boundary core. The proton concentration and mobility that are obtained from the electrostatic potential and energy barrier are used to calculate the proton conductivities in the bulk and at the grain boundary. The calculated proton conductivities are consistent with the experimentally measured proton conductivities in the bulk and at the grain boundaries of barium zirconate. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: TOTAL-ENERGY CALCULATIONS; AUGMENTED-WAVE METHOD; SPACE-CHARGE; BASIS-SET; BAZRO3; CONDUCTORS; DISTRIBUTIONS; DIFFUSION; DEFECT